A música é uma linguagem?: um estudo sobre o discurso musical no contexto do século XX - Rinaldi, Arthur [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The XXth-century Western Art Music has been the object of many studies, however, the widespread vision that this is an extremely plural repertoire tends to isolate the different aesthetical-compositional trends. If this perspective has allowed many advances regarding the knowledge of their particularities, it also has hindered the comprehension of their similarities and confluences. Particularly important is the fact that contemporary musical compositions, regardless of the trends they are associated with, are the product of compositional strategies that aim to establish some kind of dialogue with the listeners, from the concert hall public to the professional theorist/analyst. The starting point for this dialogue is the constitution of a qualitative leap, where the different sound materials are perceived as integrating a larger and more complex unity, the musical composition, which is only possible if it is established come correlation between the formal organization of the composition and the interpretative capacities of the listener. It is up to the fields of Musical Theory and Analysis to ponder upon this matter, nonetheless they are themselves as complex as the contemporary musical plurality they try to comprehend: nowadays, there is a considerable diversity of analytical tools, which are based on distinct (even conflicting) theoretical grounds. Against this seeming frame of total relativity regarding the possibilities of comprehension of the contemporary musical repertoire, it is proposed here that there are patterns of musical organization that transcend the stylistic differences, which can be grasped from the perspective that music is a language. This thesis is supported by the discussion of a group of central tenets: 1) that the processes of musical listening and musical analysis are directly dependant of a system of categorization structured around our perceptual and cognitive mechanisms ...

A música erudita ocidental do século XX tem sido objeto de muitos estudos, no entanto, a perspectiva difundida de que este é um repertório de pluralidade extrema tende a isolar as diferentes vertentes estético-composicionais. Se por um lado esta perspectiva trouxe grandes avanços no conhecimento das peculiaridades de cada vertente, por outro lado ela tem impedido a reflexão sobre suas similaridades e confluências. Particularmente importante é o fato de que as obras musicais contemporâneas, independentemente da vertente à qual pertencem, são fruto de estratégias composicionais que almejam algum tipo de diálogo com seus ouvintes, do frequentador da sala de concerto, ao teórico/analista profissional. Este diálogo tem como ponto de partida a constituição de um salto qualitativo, onde os diferentes materiais sonoros são percebidos como integrantes de uma unidade maior e mais complexa, a obra musical, cuja percepção somente é possível se for estabelecida alguma correlação entre a organização formal da obra e as capacidades interpretativas do ouvinte. Cabe aos campos da Teoria e da Análise Musical a consideração desta questão, entretanto, eles se mostram tão complexos quanto a própria pluralidade sonora contemporânea que tentam compreender uma vez que há, na atualidade, uma grande diversidade de ferramentas analíticas que se baseiam em arcabouços teóricos distintos, muitas vezes conflitantes. Buscando confrontar este quadro de aparente relativismo total em relação à possibilidade de compreensão do repertório contemporâneo, consideramos que há padrões de organização musical que transcendem as diferenças estilísticas, os quais podem ser compreendidos a partir da perspectiva de que a música é uma linguagem. Este trabalho busca defender esta tese, partindo da discussão de um conjunto de pressupostos a ele relacionados: 1) que os processos de escuta e de análise ...
Keywords: Teoria musical; Música - Séc. XX; Musica - Analise, apreciação; Linguagem; Music 20th century